2020
DOI: 10.1155/2020/5916168
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of Shugan Xiehuo Formula in the Female Rat Model with Central Precocious Puberty

Abstract: Central precocious puberty (CPP) severely affects children’s physical and mental health and needs to be treated promptly and effectively. This article aimed to research the therapeutic effect of Shugan Xiehuo Formula (SXF) on CPP. A female CPP rat model was established and then treated with leuprolide and different doses of SXF. Sex organ volume and index were measured. Ovaries and uteri were visualized by hematoxylin-eosin staining. The concentrations of follicle-stimulating hormone (FSH), luteinizing hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results showed that the Fuyou formula alleviated the symptoms in rats with PP and downregulated the GPR54/GnRH signaling pathway in GT1-7 cells. In another study, Yin et al evaluated the therapeutic effect of the Shugan Xiehuo formula containing 10 herbs in a female rat model with PP [ 27 ]. Treatment with Shugan Xiehuo reduced the serum level of gonadotropic hormones in PP rats and suppressed the expression of GnRH, GnRH receptor, estrogen receptor subtype α, and G protein-coupled receptor 30 in the hypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the Fuyou formula alleviated the symptoms in rats with PP and downregulated the GPR54/GnRH signaling pathway in GT1-7 cells. In another study, Yin et al evaluated the therapeutic effect of the Shugan Xiehuo formula containing 10 herbs in a female rat model with PP [ 27 ]. Treatment with Shugan Xiehuo reduced the serum level of gonadotropic hormones in PP rats and suppressed the expression of GnRH, GnRH receptor, estrogen receptor subtype α, and G protein-coupled receptor 30 in the hypophysis.…”
Section: Discussionmentioning
confidence: 99%